Direct selling success : from amway to zombies - Gage, Randy (Wiley, 2019)
"The eagerly awaited sequel to the worldwide bestseller How to Build a Multi-Level Money Machine from Direct Selling icon and Hall of Famer Randy Gage Randy Gage revolutionized the Direct Selling profession with the bestselling phenomenon How to Build a Multi-Level Money Machine, translated into more than 20 languages. Now hes at it again with the long-waited sequel: Direct Selling Success. This all-new book is the ultimate textbook on creating success in the business. Youll learn everything from choosing the right company, finding the best candidates, becoming a rock star recruiterto advanced skills like making powerful presentations, becoming a leader, and creating a leadership factory on your team. Since Randys previous book took the profession by storm, there have been significant changes to the business that demand a fully up-to-date sequel: Regulatory oversight of the industry has increased dramatically, its now much trickier to make simple product or income claims, and distributors are hungry for the right information on how to get it done. The business model has gained widespread public acceptanceits now common for industry companies to secure naming rights for sports arenas and sponsor major league teams. Even Warren Buffet and Forbes Magazine promote the business. More and more people are taking on side hustles and are considering or already in the business.Maybe the biggest change is the impact of e-commerce, social media, and mobile apps on the business today. Randys up-to-the-minute book explains how you can become successful in this new environment. The need for expert, proven guidance on the Direct Selling and Network Marketing profession has never been greater than right now. Direct Selling Success will help you: Choose the best company for you Locate the best candidates Become a Rock Star recruiter Design your system to create maximum duplication Employ the latest e-commerce and social media marketing techniques to grow your business Conduct powerful persuasive presentations Become a positive, dynamic leader for your team The Direct Selling industry continues to experience robust growth. The opportunity to generate passive income and create complete financial freedom is immense under current conditions. Direct Selling Success is a must-have resource for anyone who wants to build a team of customers and distributors that will generate residual income for years to come"--